Legal Protection of Personal Data and Virtual Assets in the Metaverse: A Comparative Study of the United States, China, and South Korea - Kandriana, Muhammad; Zuhrah , Zuhrah; Iksan , Iksan; Maulana, Rahmad; Yasir, Muhammad (Faculty of Sharia and Law, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
The development of the metaverse as a new digital interaction space has given rise to increasingly complex legal challenges regarding the protection of personal data and virtual assets. This situation demonstrates the regulatory gap between countries in responding to the dynamics of the global digital economy. This study examines the comparison of regulations on personal data protection and virtual asset protection in the United States, China, and South Korea, and identifies lessons that can be applied to the Indonesian legal system. Utilizing a normative legal research method through a comparative approach, this study examines primary and secondary legal sources, including laws, national policies, and digital legal doctrines, in each country. The results show that the United States applies a liberal sectoral regulatory model, China adopts a centralistic model based on state control, while South Korea develops a hybrid model that balances innovation and legal protection. The comparative analysis reveals gaps in institutional aspects, regulatory integration, and legal recognition of activities and assets in the metaverse. The results of the study indicate that Indonesia should adopt an adaptive legal framework that comprehensively integrates personal data and virtual asset protection as a guiding principle for ius constituendum in establishing a safe, equitable, and globally competitive metaverse governance.